The 100th anniversary of the Federal Scientific Vegetable Center, the leader of Russian scientific vegetable growing - A. V. Soldatenko; F. B. Musaev; D. V. Sokolova (Труды по прикладной ботанике, генетике и селекции)
This year, the staff of the Federal Scientific Vegetable Center (FSVC) celebrates their 100th anniversary. Prof. S. I. Zhegalov was the recognized founder of the institution, which was reorganized from Gribovo Vegetable Experimental Station. Its team started with 14 employees, and the experimental crop area was slightly less than 4 hectares. In a short period of time (1920 to 1927), 74 cultivars of the most popular vegetable crops and a number of flower crop varieties were developed and improved. The second period of the Station’s development (1937 to 1966) was associated with the name of Acad. E. I. Ushakova. During this period, a pleiad of talented scientific plant breeders emerged and thrived: A. V. Alpatyev, S. P. Agapova, E. M. Popova, A. D. Plinka, Yu. A. Kobyakova, and others. In 1971, Gribovo Experimental Station was transformed into the All-Union Scientific Research Institute for Breeding and Seed Production of Vegetable Crops (VNIISSOK). The Institute was headed by Acad. P. F. Sokol. Under his leadership, capacity building and logistic support of the Institute were promoted: new facilities were built, and the experimental production network was expanded. Despite the difficulties associated with the reorganization and the financial and political situation in the country in 1992–2017, the staff achieved significant results during the years of the directorship by Acad. V. F. Pivovarov. New cultivars were developed to meet the demand; they occupied more than 50% of the crop area under vegetables across the country. Each year, the Institute produced 200–300 tons of elite and cultivar seeds. In 2017, the Institute was merged into the Federal Scientific Vege table Center as the keystone element. The Center also incorporated the All-Russian Research Institute of Vegetable Production and seven experiment stations throughout the Russian Federation. The Institute has been successfully cooperating with the N.I. Vavilov Institute of Plant Genetic Resources (VIR) for many years, exchanging germplasm materials and experience, and jointly developing vegetable cultivars.